FEAR OF SOCIAL ALIENATION OF LOVE AS GENDER CHARACTERISTICS - V. V. Melnyk; L. І. Моzhovyi; I. A. Reshetova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The paper considers the fear of social alienation of love. It is within the limits of psychoanalytic epistemology, the analysis of which will be presented in the article, the tendencies to monotony and universal solutions with an emphasis on ensuring the objectivity of the problem of gender alienation, to be more exact, the fear of love, which causes the gender process, are viewed most reliably. In view of the above the purpose of the paper is to investigate the conceptual contradictions associated with the reconstruction of basic measurements of the fear of alienation of love within different ideological approaches; to reveal the most significant contradictions that manifest themselves in the differences between secular and religious frames; to determine a philosophical and fundamental foundation for the types of fear: metaphysical, transcendental and social, which to some extent have influenced the development of a gender tradition. The paper investigates the fear of alienation of love, not as an instinct or psychological experience, or as a social factor, but as a correlation between the functional types of fear and the peculiarities of social and cultural processes, and it acts as a dependence of the European societies on the various functional forms of fear of love that influence the processes of social transformations. Theoretical basis. The authors determine that in the gender approach the subject, who is cognized, has specific desires and interests. The process of cognation is local, contextual, in which physiologically and spiritually the fear of alienation of love is closely linked to the conditions of existence of people, with the arrangement of social and individual life. In modern civilization, true love with some exceptions, is fleeting. It is now hindered by the burdens of life, and ideological settings, which go only from the "I", and not from the common "I and You", contributing to frustration and alienation. Originality. The emphasis is placed on the fact that the fear of alienation of love, as a way of identifying the essential characteristics of "I", acts as an existential, which concentrates on the sense-life range of problems. The range of problem in a single topic is in the "point I", surrounded by gender boundaries, it contains as a condition for its manifestation the personality distancing – free (self) or forced (isolation) consolidation and assertion of the autonomy of the individual. Alienation of love as an existential admits in the register of the intimate, intentional for self-perception, internal state to organize and identify with the "authentic I". Conclusions. The article establishes that gender identity under the conditions of modern socio-psychological crisis is associated with forming a special "picture of fear, anxiety, loneliness" as a part of that internal and external world, generated by alienation from society. The fear of alienated love acts as the essential existential of human being, which is a necessary existential condition of the existential tension that occurs as an antipode and a characteristic of courage, asceticism, and the "beginning of wisdom". The considered phenomenon of the fear of alienation of love is interpreted as the result of the ontological and gender alienation of a person who has lost a sense of security (due to the collapse of the value universe) and plunged into a continuous interindividual rivalry.